2012
DOI: 10.1016/j.ksujds.2012.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Quality of communication between dentists and dental technicians for fixed and removable prosthodontics

Abstract: Objective: The aim of this study was to evaluate the quality of communication between dental practitioners and dental technicians through work authorizations and selection of impression trays and materials for both fixed and removable prosthodontics in the Dental College of King Saud University.Methods and materials: A questionnaire was distributed to the dental technicians concerning the quality of written instructions in the work authorization form. Use of impression trays and materials for fixed and removab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
11
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 19 publications
(48 reference statements)
4
11
1
Order By: Relevance
“…It was left to the technician in almost 72.7% of the cases which may affect the ultimate functional and aesthetic outcomes. The results of this study are generally in line with surveys conducted in various regions of the world (Al-AlSheikh, 2012;Aslam & Ahmed, 2015;Avrampou et al, 2012;Berry et al, 2014b;Cotmore, Mingledorf, Pomerantz, & Grasso, 1983;Dickie et al, 2014;Haj-Ali, Al Quran, & Adel, 2012;Radhi et al, 2007;Schwarz & Barsby, 1980).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…It was left to the technician in almost 72.7% of the cases which may affect the ultimate functional and aesthetic outcomes. The results of this study are generally in line with surveys conducted in various regions of the world (Al-AlSheikh, 2012;Aslam & Ahmed, 2015;Avrampou et al, 2012;Berry et al, 2014b;Cotmore, Mingledorf, Pomerantz, & Grasso, 1983;Dickie et al, 2014;Haj-Ali, Al Quran, & Adel, 2012;Radhi et al, 2007;Schwarz & Barsby, 1980).…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, disinfection status of the items was mentioned in only 9.3% of the cases (8.3% positive, 1% negative). These results were similar to those of other studies (Al-AlSheikh, 2012;Radhi, Lynch, & Hannigan, 2007;Scully, Moles, & Fiske, 2007). Al-Kheraif evaluated infection control in Riyadh, Saudi Arabia, and reported that the impressions referred to 9.4% of laboratories were not disinfected (Al-kheraif, 2008) and laboratories did not even receive any feedback on disinfecting process in 90.6% of the cases.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…It is possible that dentists put a greater emphasis on CC-RPD instructions than A-RPD instructions because of the high cost of CC-RPDs, or because CC-RPDs were prescribed by dentists who possessed greater skills than those who prescribed A-RPDs. The results of this research showed that most of the design components for A- and CC-RPDs were not clearly prescribed, which again is similar to previous studies ( 13 , 17 , 23 , 24 ). This again indicates that dentists leave it mainly to technicians to design the prosthesis, which is unacceptable as the dentists should be fully responsible for the RPD design, since they perform the examination, diagnosis, and treatment planning.…”
Section: Discussionsupporting
confidence: 88%
“…These findings are disappointing as CC-RPDs are more proficient in maintaining oral health than A-RPD, and the latter may even have harmful effects on the oral tissues ( 10 , 18 , 19 ). Reasons for the frequent prescription of A-RPD may be the high financial cost of CC-RPD and lack of educational or clinical experience in constructing CC-RPD ( 13 ). Based on the number of design components, most of the A- and CC-RPD instructions in the current study were not considered clear.…”
Section: Discussionmentioning
confidence: 99%